2018
DOI: 10.1111/ppl.12734
|View full text |Cite
|
Sign up to set email alerts
|

A role for ALF4 during gall and giant cell development in the biotic interaction between Arabidopsis and Meloidogyne spp.

Abstract: Root-knot nematodes (RKNs; Meloidogyne spp.) are a major pest for the agriculture worldwide. RKNs induce specialized feeding cells (giant cells, GCs) inside galls which are de novo formed pseudo-organs in the roots that share similarities with other developmental processes as lateral root (LR) and callus formation or grafting involving new vascular development or pericycle proliferation. Hence, it is pertinent to study the molecular mechanisms directing the plant-nematode interaction. In this respect, ALF4 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
(102 reference statements)
0
11
0
Order By: Relevance
“…How the nematode achieves these massive structural changes in the roots remains unclear. We have recently reported the formation of nematode feeding‐sites in Arabidopsis leaves, consisting of callus‐like structures containing GCs (Olmo et al , 2017a), the induction of ALF4 and also the formation of aberrant small GCs in the alf4‐1 mutant in root galls (Olmo et al , 2019). Activation of ALF4 is also necessary during LR development (DiDonato et al , 2004), for CIM‐C formation or during grafting (Sugimoto et al , 2010; Melnyk et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…How the nematode achieves these massive structural changes in the roots remains unclear. We have recently reported the formation of nematode feeding‐sites in Arabidopsis leaves, consisting of callus‐like structures containing GCs (Olmo et al , 2017a), the induction of ALF4 and also the formation of aberrant small GCs in the alf4‐1 mutant in root galls (Olmo et al , 2019). Activation of ALF4 is also necessary during LR development (DiDonato et al , 2004), for CIM‐C formation or during grafting (Sugimoto et al , 2010; Melnyk et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, those genes coregulated with LBD16 in GCs and galls showed a similar expression profile in those pluripotent cells of the CIM‐C (Cabrera et al , 2015). Some regenerative capacity of galls has also been described; for example, LRs/ARs develop from the galls in Col‐0 and also from mutants severely impaired in LR formation ( arf7/arf19 , slr or alf4 ), but only from the gall zone (Olmo et al , 2017a, 2019). Infected poplar roots also developed new suckers from galls (Baldacci‐Cresp et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have been working for decades to identify the factors from both the nematodes and the host plants that contribute to this process (Sandstedt and Schuster , Bird and Saurer ). From their previous work, Olmo et al () found that the gene expression pattern during giant cell formation matches closely to the reprogramming that occurs during callus formation. The giant cells also grow an extensive network of vasculature around them to ensure the supply of nutrients; a process that resembles vasculature development following grafting.…”
mentioning
confidence: 80%